Effect of Citrus Sinensis Aromatherapy on Pain and Anxiety Among Hemodialysis Patients: A Quasi-Experimental Study - Ariningpraja, Rustiana Tasya; Fatma, Endah Panca Lydia; Lestari, Retno (Journal of Applied Nursing and Health, 2026)
Background: Pain is a common problem in hemodialysis patients and is often accompanied by anxiety. Aromatherapy is a simple, low-cost complementary intervention, but evidence in hemodialysis patients is still limited and inconclusive. Citrus sinensis essential oil is of particular interest because its major bioactive components are analgesic and anxiolytic agents. The purpose of this study was to determine the effect of citrus sinensis aromatherapy on pain and anxiety in hemodialysis patients. Methods: A quasi-experimental design with a control group included 50 hemodialysis patients (25 control and 25 intervention) selected by purposive sampling at the Bangil Health Centre in Pasuruan City. Eligible patients were ≥ 18 years old, have good sense of smell, on routine hemodialysis. Pain was measured using the Numeric Rating Scale (NRS) and anxiety using the Generalized Anxiety Disorder-7 (GAD-7)—data analyzed with a paired t-test. The intervention was given twice a week for 30 minutes. Ethical clearance was obtained. Results: In the intervention group, mean pain score decreased from 6.2 ± 1.1 to 3.4 ± 1.0, and anxiety scores decreased significantly (both p < 0.001), while changes in the control group were not significant. Between-group comparisons showed a greater reduction in pain and anxiety in the intervention group (p < 0.05). Conclusion: The Citrus sinensis aromatherapy was effective to reduce on pain scale and anxiety level in chronic kidney disease patients undergoing hemodialysis. These findings suggest that citrus sinensis aromatherapy can be considered as a simple complementary nursing intervention to improve comfort and psychological well-being during hemodyalisis period.